Intrathoracic tuberculous lymphadenopathy: clinical and bronchoscopic features in 17 adults without parenchymal lesions. Issue 1 (January 1996) - Baran, R.; Tor, M.; Tahaoğlu, K.; Ozvaran, K.; Kir, A.; Kizkin, O.; Türker, H.
Abstract : BACKGROUND: Whilst intrathoracic lymphadenitis is a characteristic sign of primary tuberculosis in children, its presence without parenchymal lesions in adults is unusual and makes the diagnosis using noninvasive techniques difficult. The diagnostic role of bronchoscopy in adults with intrathoracic tuberculous lymphadenitis is reported. METHODS: Seventeen patients with intrathoracic lymphadenopathy seen during 1993 who had all undergone bronchoscopy and had been found to have tuberculosis in the absence of any parenchymal lung lesions were evaluated retrospectively. RESULTS: Right paratracheal lymphadenopathy was observed on the plain chest radiograph in all the patients. Fifteen of the 17 patients had an endobronchial abnormality and samples taken at bronchoscopy gave a definitive diagnosis in nine (53%) of the 17. Four patients had ulcerating endobronchial granuloma and all had biopsy samples positive for tuberculosis. Transbronchial or transcarinal needle aspiration samples were diagnostic in five of 11 patients (45%) subjected to the procedure. Peripheral lymph node biopsy diagnosed tuberculosis in two cases and in the remaining six patients the diagnosis wa achieved by mediastinoscopy or thoracotomy. CONCLUSIONS: Bronchoscopy has an important role in the diagnosis of intrathoracic tuberculous lymphadenopathy in adults and should be considered before other invasive procedures.